2015
DOI: 10.1002/trtr.1374
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Academic Vocabulary Words Worth Learning

Abstract: Fisher and Frey have developed, implemented, and refined a process for teachers and students that results in evidence becoming a signature part of student work.You'll see how scaffolding these skills, which often are not learned until college or the workplace, can improve your students' reading and writing, both in terms of the habits they develop and in the writing they produce. QR codes within the book link to videos of classroom strategies in action, teacher ideas, and chapter introductions from the authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The aim of this section is to discuss the results of this investigation in light of the literature review. Taking into account that vocabulary is considered one of the main issues in EAP learning (Gass and Selinker, 2008;Cobb and Horst, 2015;Townsend and Kiernan, 2015), many authors have set to compile word lists that could be useful for students to evaluate their own texts; and for teachers when considering which words to focus their teaching on. In the second part of this study, one of those lists was used as a reference in a corpus of Brazilian students' writings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this section is to discuss the results of this investigation in light of the literature review. Taking into account that vocabulary is considered one of the main issues in EAP learning (Gass and Selinker, 2008;Cobb and Horst, 2015;Townsend and Kiernan, 2015), many authors have set to compile word lists that could be useful for students to evaluate their own texts; and for teachers when considering which words to focus their teaching on. In the second part of this study, one of those lists was used as a reference in a corpus of Brazilian students' writings.…”
Section: Discussionmentioning
confidence: 99%
“…This section will offer an overview into studies on the role of vocabulary in language learning. Several studies (Gass and Selinker, 2008;Cobb and Horst, 2015;Townsend and Kiernan, 2015) argue that having ample lexical knowledge grants better reading and writing skills for students of English as a Foreign Language (EFL). Research on the influence of vocabulary in schoolaged children's reading comprehension (Garcia, 1991;Snow, 2010;Stahl and Fairbanks, 1986) confirms the impact of general academic vocabulary in students' achievement.…”
Section: The Role Of Vocabulary In Language Learningmentioning
confidence: 99%
“…However, these literacy skills are quite different from those needed to read and interpret a periodic table in science class or write a proof in a geometry course. Townsend and Kiernan (2015) described academic vocabulary as "abstract, technical, nuanced, and/or densely packed with meaning" (p. 113). Because of the complex nature of terms in content area courses, studies have been conducted to determine effective ways of introducing and engaging students in this type of Miranda L. Sigmon, sigmonm@winthrop.edu, is an assistant professor at Winthrop University in Rock Hill, South Carolina.…”
Section: Discipline-specific Vocabularymentioning
confidence: 99%
“…Further research conducted on the usefulness of academic words confirms these arguments, indicating the supportive role of academic words in English academic texts (Campion & Elly, 1971;Cowan, 1974;Durrant, 2016;Farrell, 1990;Hutchinson & Waters, 1987;Nagy & Townsend, 2012;Nassaji, 2006;Praninskas, 1972;Staehr-Jensen, 2005;Trimble, 1985). For example, it has been found that academic vocabulary plays a role in L2 learners' academic achievements (Garcia, 1991;Li & Pemberton, 1994;Qian 1999Qian , 2002Snow, 2010;Stahl & Fairbanks, 1986), reading comprehension (Clark & Ishida, 2005;Park, 2012), writing skills (Cobb & Horst, 2015;Engber, 1995;Gass & Selinker, 2008;Gonzalez, 2013;Grobe, 1981;Shaw, 1991;Townsend & Kiernan, 2015) and academic English proficiency (Townsend, Filippini, Collins, & Biancarosa, 2012).…”
Section: Academic Vocabularymentioning
confidence: 99%